2016
DOI: 10.3102/0013189x16644606
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Consequences of Oversimplifying Educational Inequities

Abstract: In this technical comment, we argue that Morgan et al.’s claim that there is no minority overrepresentation in special education is in error due to (a) sampling considerations, (b) inadequate support from previous and current analyses, and (c) their failure to consider the complexities of special education disproportionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 23 publications
1
130
2
Order By: Relevance
“…In general, results support previous research that suggests non‐Hispanic Black children are more likely to be identified as children needing specialized services, especially for behavior (e.g., Donovan & Cross, ; Sullivan & Bal, ) but are contrary to more recent analysis of the issue using an ECLS data set that reported Black children are underrepresented in special education and in ED, specifically (Morgan et al, ). Recent review and commentaries, however, have challenged the validity of their methodology and inferences (for discussion, see Cruz & Rodl, ; Skiba et al, ; Sullivan, ). This could be a result of the additional controls used in their model or the difference in the coding of the outcome in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, results support previous research that suggests non‐Hispanic Black children are more likely to be identified as children needing specialized services, especially for behavior (e.g., Donovan & Cross, ; Sullivan & Bal, ) but are contrary to more recent analysis of the issue using an ECLS data set that reported Black children are underrepresented in special education and in ED, specifically (Morgan et al, ). Recent review and commentaries, however, have challenged the validity of their methodology and inferences (for discussion, see Cruz & Rodl, ; Skiba et al, ; Sullivan, ). This could be a result of the additional controls used in their model or the difference in the coding of the outcome in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found nonsignificant effects of SES after controlling for other child and school‐level factors (Kincaid & Sullivan, ; Skiba, Poloni‐Staudinger, Simmons, Renae feggins‐Azziz, & Chung, ), whereas others primarily attribute over representation of Black children in special education to the disadvantages of poverty (Morgan et al, ). The history of contrary results suggests a complex interplay between race and SES in special education eligibility (Skiba et al, ), a matter that has long been challenged in the disproportionality literature (e.g., Skiba et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, parents of color experience limited opportunities to participate in key educational decisions such as those made during IEP meetings, as well as marginalization due to their identities as low-income parents of color (Harry & Klingner, 2006;OngDean, 2009). In addition, the disproportional representation of Black, Latinx, and Native American students in special education continues to be an unresolved conundrum (Skiba, Artiles, Kozleski, Losen, & Harry, 2015). Thus, school choice is implemented in a context fraught with historical legacies of racism and ableism.…”
Section: School Choice or The Politics Of Desperation? Black And Latimentioning
confidence: 99%
“…This is an urgent need in an educational system that continues to use special education as a tool to sort children who challenge teachers' skills and understanding of how sociocultural backgrounds, language, and experience alter assumptions about the tacit knowledge that students bring to the classroom (Kozleski, Artiles, & Skrtic, 2014). Researchers have highlighted the relationship between cultures in classrooms and the cultural and linguistic backgrounds of students in relationship to who is referred and identified for special education (Artiles, Kozleski, & Waitoller, 2011;Donovan & Cross, 2002;Skiba, Artiles, Kozleski, Losen, & Harry, 2016). While two recent publications offer evidence that questions the degree to which racial disproportionality exist within special education, a number of scholars in the area concur that recent research is flawed (Skiba et al, 2016).…”
Section: The Cultural Work Of Teacher Educationmentioning
confidence: 99%
“…Researchers have highlighted the relationship between cultures in classrooms and the cultural and linguistic backgrounds of students in relationship to who is referred and identified for special education (Artiles, Kozleski, & Waitoller, 2011;Donovan & Cross, 2002;Skiba, Artiles, Kozleski, Losen, & Harry, 2016). While two recent publications offer evidence that questions the degree to which racial disproportionality exist within special education, a number of scholars in the area concur that recent research is flawed (Skiba et al, 2016). Disproportionate representation of students of color and other unrepresented groups remains a critical benchmark for assessing whether US schools are successful for some or all students.…”
Section: The Cultural Work Of Teacher Educationmentioning
confidence: 99%